2019
DOI: 10.1002/jgh3.12176
|View full text |Cite
|
Sign up to set email alerts
|

Does esophageal wall thickness on computed tomography predict response to endoscopic dilatation in patients with corrosive esophageal strictures?

Abstract: Background and Aim To evaluate the role of esophageal wall thickness (EWT) on computed tomography (CT) in predicting response to endoscopic dilatation of corrosive esophageal strictures. Methods This was a retrospective study. A review of the records of patients who underwent endoscopic dilatation of esophageal strictures between January 2010 and December 2017 was performed. Patients who had a CT evaluation prior to dilatations were included. CT‐EWT was measured at the maximum visible point. Clinical details a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…One research project carried out in Karachi, which involved participation from a total of twenty-seven patients. Endoscopic dilatation with a Savary-Gilliard dilator was performed, and this helped twenty-two out of twenty-seven patients (81.4%) with their dysphagia [13][14].…”
Section: Discussionmentioning
confidence: 99%
“…One research project carried out in Karachi, which involved participation from a total of twenty-seven patients. Endoscopic dilatation with a Savary-Gilliard dilator was performed, and this helped twenty-two out of twenty-seven patients (81.4%) with their dysphagia [13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the use of CT scans of the chest and abdomen is increasing. CT can assist prognosis after ingestion, but it is still inconclusive [25][26][27]. CT also provides extraesophageal information regarding anatomies such as the mediastinum, lung, and pleural cavity, which endoscopies do not (Table 2).…”
Section: Managementmentioning
confidence: 99%
“…They found that patients with maximal wall thickness ≥ 9 mm required more dilations. However, a recent study of 64 patients with corrosive strictures showed that median CT esophageal wall thickness was 7 mm (range 3 -22 mm) and that it did not predict technical or clinical success, refractory or recurrent strictures and adverse events of endoscopic dilation [5]. CT can evaluate overall wall thickness, but it cannot delineate the wall layers and hence their degree of involvement.…”
Section: Eus Mini-probe Layers Of Esophageal Wall Involvementmentioning
confidence: 99%
“…Techniques that have been studied to predict response to endoscopic dilations include contrast-enhanced computed tomography (CECT) scans and endoscopic ultrasound (EUS). Esophageal wall thickness (EWT) on CECT has been found to correlate with response to dilation in one study [4] but not in another [5]. EUS, using radial probe, placed at the proximal margin of the stricture, has been used to predict response to dilation based on the depth of tissue injury, i. e. the number of layers of esophageal wall involved [6].…”
Section: Introductionmentioning
confidence: 99%